The current utilization and perceptions of prescription drug monitoring programs among emergency medicine providers in Florida - Henry W. Young; Joseph A. Tyndall; Linda B. Cottler (International Journal of Emergency Medicine, 2017)
Abstract Background Pain is among the most commonly treated symptoms in the emergency department, and opioids are commonly prescribed from the emergency department to treat moderate to severe pain. Prescription drug monitoring programs (PDMP) can be used to assist physicians identify individuals at increased risk to misuse or abuse opioids. While the use of the PDMP has been shown useful among clinicians, in the past, utilization of the PDMP has been less than optimal. The objective of this study was to assess the current utilization and perceptions of the prescription drug monitoring program among emergency medicine providers in Florida. Methods A survey assessing the utilization and perception of Florida’s prescription drug monitoring program was distributed to emergency medicine providers in Florida over a 5 week period. Attending physicians, physicians in training, and extenders from a variety of practice types were assessed. Results A total of 88 surveys were completed. Over two thirds (67%) of the respondents were male. The majority of respondents were attending physicians (62%), 13 (14%) were residents, and 21 (23%) were extenders. Nearly all (99%) were aware of Electronic-Florida Online Reporting of Controlled Substance Evaluation Program (EFORCSE) and 84% had registered accounts. More than 2/3 (73%) reported feeling pressured to prescribe opioids, and 70% reported receiving no formal education on identifying individuals at increased risk of opioid misuse. Approximately half (51%) reported that they used EFORCSE only when they suspect the patient may misuse the medication, 21% reported that they rarely used EFORCSE, and only 3% reported using PDMP every time that they prescribed opioids. Residents used PDMP less frequently than extenders and attending physicians. The most common barriers associated with PDMP use were related to access. Conclusions Although most providers reported that they were aware of their states’ PDMP, utilization of the PDMP among emergency medicine providers in Florida remains low. Low utilization was associated with barriers to access. If further enhancements to PDMPs can be made to improve accessibility, then rates of PDMP utilization may increase.